Phytoremediation potential of Milk thistle (Silybum marianum) - A sustainable approach to mitigate soil contamination while supporting pharmaceutical applications - Cvetkovikj, Ivana; Gjorgjievska, Jovana; Todorovska, Marija; Todorov, Filip; Stoilkovska Gjorgievska, Veronika; Karapandzova, Marija; Markoski, Mile; Stefkov, Gjoshe (My University, 2025)
Milk thistle (Silybum marianum) is recognized for its medicinal properties and potential as a phytoremediation agent. [1,2] This study assesses its ability to absorb heavy metals and decontaminate soils while preserving pharmacological efficacy. Soil and plant samples were collected from eight locations in North Macedonia during different vegetative phases. Mechanical and pedological soil analyses were conducted to characterize soil composition, while heavy metal concentrations in soil and plant material were evaluated using ICP-AES. Silymarin content in the plant and seeds was determined via high-performance liquid chromatography (HPLC). The soils exhibited significant variability in heavy metal content. Lead (Pb) levels ranged from 25 to 107 mg/kg, cadmium (Cd) from 0.1 to 1.3 mg/kg, and zinc (Zn) from 14 to 203 mg/kg. Notably, lead and cadmium levels in plant material were below detection limits, confirming minimal accumulation, whereas zinc levels varied significantly, peaking in urban areas. Silymarin content ranged from 0.02% to 0.16% in plant material, with seeds exhibiting higher concentrations (1.14%), demonstrating the plant's resilience and pharmacological viability in contaminated environments. These results highlight the adaptability of milk thistle to diverse soil conditions and its capacity to accumulate metals without compromising silymarin production. By combining phytoremediation with medicinal plant cultivation, milk thistle offers a sustainable approach to mitigating soil contamination while supporting pharmaceutical applications. This study provides critical insights for integrating environmental restoration with the production of high-value medicinal plants.